The Socialist People's Libyan Arab Jamahiriya : 2006 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for The Socialist People's Libyan Arab Jamahiriya. (IMF Staff Country Reports; Country Report, 2007)
This 2006 Article IV Consultation highlights that Libya has made efforts to liberalize its economy and foreign trade, achieving increasing economic growth while maintaining macroeconomic stability. In 2006, economic conditions continued to be satisfactory. Real GDP grew about 5 1\2 percent, reflecting an increase of 4 1\2 percent in the value added of the hydrocarbon sector. In 2006, structural reform continued with the implementation of a wide range of measures covering fiscal management and taxation, banking and payments systems, trade, and the business environment.